Alfonsas Nyka-Niliunas’ Intellectual Provisions in Texts, Diaries and Correspondence from the Late 1950’s to Mid 1980’s - Blockutė, Emilija (Vilnius University Open Series, 2024)
The text explores the intellectual provisions of the poet Alfonsas Nyka-Niliunas, which began to emerge in the 1940s in the cultural press, and took on a clear form in the 1950s with the publication of the literary magazine “Literatūros lankai”. Nyka-Niliūnas continued to adhere to his intellectual provisions and the evaluations they dictated in the later stages of his life. The article presents Nyka-Niliūnas not only as a poet and translator, but also as an active shaping force in the cultural field and the literary canon, and presents the principles of his work. The analysis also includes fragments of Nyka-Niliūnas’s diary “Dienoraščio fragmentai”, which are proposed to be treated as an autobiographical construction. The article also presents life experiences that did not make it into Nyka-Niliūnas’ published diary, which allows for a new look at Nyka-Niliūnas and the self-representational image he creates.
Keywords: Alfonsas Nyka-Niliūnas; history of literature; intellectual history; biography; egodocuments